Fate and Impact of Microplastics in Marine Ecosystems 2017
DOI: 10.1016/b978-0-12-812271-6.00181-2
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Sewage Sludge: Effects of Treatment

Abstract: 28This study highlights the potential for sewage sludge treatment processes to affect the risk of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 0 publications
3
94
2
4
Order By: Relevance
“…In the U.S., approximately 60% of wastewater sludge (also known as biosolids) is applied on agricultural fields, reclamation sites, or sold directly to consumers for use on gardens and landscaping. Mahon et al () reported microplastic burdens of 4,196 to 15,385 microparticles kg −1 in Irish sludges destined for land application. Repeated applications on the same plot (common for fertilizers) increased proportionately the abundance of microplastics in receiving soils (Corradini et al, ).…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
“…In the U.S., approximately 60% of wastewater sludge (also known as biosolids) is applied on agricultural fields, reclamation sites, or sold directly to consumers for use on gardens and landscaping. Mahon et al () reported microplastic burdens of 4,196 to 15,385 microparticles kg −1 in Irish sludges destined for land application. Repeated applications on the same plot (common for fertilizers) increased proportionately the abundance of microplastics in receiving soils (Corradini et al, ).…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
“…particles are concentrated in the solid sludge phase 8,9 , which is often applied to agricultural soils as 33 fertiliser. Nizzetto et al 10 estimate that between 63,000-430,000 and 44,000-300,000 tons of 34 microplastic are added per year to farmlands in Europe and North America respectively.…”
Section: Introduction 28mentioning
confidence: 99%
“…agricultural soils may represent a major environmental reservoir of microplastic. A small number of 36 studies have examined microplastics in soil [11][12][13][14] and sludge samples [7][8][9][15][16][17][18][19][20][21] , but no standardised method 37 has emerged. The organic components, complexity of the solid matrix, and presence of additional 38 contaminants complicates the extraction of small plastic particles 22 .…”
Section: Introduction 28mentioning
confidence: 99%
See 1 more Smart Citation
“…Sewage treatment plants, landfills, urban and industrial centres, and continental systems (i.e. terrestrial, aquatic and semiaquatic in land environments), in general, are considered diverse sources of MPs (Lechner and Ramler 2015;Mahon et al 2017;Talvitie et al 2017) The best available estimates, so far, regarding global plastic waste inputs from land-based sources into the oceans come from Jambeck et al (2015). However, several assumptions were made in this study, and it is considered that the calculations presented therein could perhaps constitute an underestimation of the reality (Horton et al 2017).…”
Section: Plastic Waste In the Marine And Terrestrial Environmentmentioning
confidence: 99%